Developing Student Worksheets (LKPD) with a Computational Approach to Improve Critical Thinking Abilities in Elementary Students of SDN 101854 Sei Mencirim - Fitriani Br Sitepu; Daulat Saragi; Yusnadi; Sri Yunita (International Journal of Educational Practice and Policy, 2026)
This study was driven by the low critical thinking skills of fourth-grade students in Pancasila Education at SDN 101854 Sei Mencirim. The issue stems from lecture-based teaching and the use of conventional worksheets (LKPD), which limit students’ practice in higher-order thinking tasks. This is reflected in daily test results on the Constitution and Norms in Society topic, where most students failed to meet the Minimum Competency Standard (KKM). Therefore, this research aims to develop a computational-based worksheet and evaluate its feasibility, practicality, and effectiveness. This study used a Research and Development (R&D) method with a 4D model, including the stages of define, design, develop, and disseminate. The results indicate that the computational-based worksheet, with its stages of decomposition, pattern recognition, abstraction, and algorithm, is valid, practical, and effective. Expert validation increased, namely material experts. from 76% to 90.6%, language experts from 68.8% to 92.8%, and media experts from 77.3% to 94%. Teachers' practicality reached an average of 88.5% (very practical). Effectiveness was evident in the increase in the average pretest score from 61 to 80.16 on the posttest, exceeding the Minimum Completion Level (KKM) of 70. Therefore, this Student Worksheet (LKPD) is suitable for use as an alternative learning medium to improve students' critical thinking skills.